Childbirth and parenting preparation in antenatal classes. (February 2018) - Barimani, M.; Forslund Frykedal, K.; Rosander, M.; Berlin, A.
Abstract: Objectives: to describe topics (1) presented by midwives' during antenatal classes and the amount of time spent on these topics and ( 2 ) raised and discussed by first-time parents and the amount of time spent on these topics. Design: qualitative; data were gathered using video or tape recordings and analysed using a three-pronged content analysis approach, i.e., conventional, summative, and directed analyses. Setting and participants: 3 antenatal courses in 2 antenatal units in a large Swedish city; 3 midwives; and 34 course participants. Findings: class content focused on childbirth preparation (67% of the entire antenatal course) and on parenting preparation (33%). Childbirth preparation facilitated parents' understanding of the childbirth process, birthing milieu, the partner's role, what could go wrong during delivery, and pain relief advantages and disadvantages. Parenting preparation enabled parents to ( i ) plan for those first moments with the newborn; ( ii ) care for/physically handle the infant; ( iii ) manage breastfeeding; ( iv ) manage the period at home immediately after childbirth; and ( v ) maintain their relationship. During the classes, parents expressed concerns about what could happened to newborns. Parents' questions to midwives and discussion topics among parents were evenly distributed between childbirth preparation (52%) and parenting preparation (48%). Key conclusions: childbirth preparation and pain relief consumed 67% of course time. Parents particularly reflected on child issues, relationship, sex, and anxiety. Female and male participants actively listened to the midwives, appeared receptive to complex issues, and needed more time to ask questions. Parents appreciated the classes yet needed to more information for managing various post-childbirth situations. Implications for practice: while midwifery services vary among hospitals, regions, and countries, midwives might equalise content focus, offer classes in the second trimester, provide more time for parents to talk to each other, allow time in the course plan for parents to bring up new topics, and investigate: ( i ) ways in which antenatal course development and planning can improve; ( ii ) measures for evaluating courses; ( iii ) facilitator training; and ( iv ) parent satisfaction surveys. Highlights: The midwifes targeted birth preparation more than parenting preparation. Parents want a balance between birth preparation and parenting preparation. Parents expressed concerns about what could happened once they are home. All participants needed more time to discuss with other parents.